Auxiliary midwives in hard to reach rural areas of Myanmar: filling MCH gaps. (December 2016) - Wangmo, Sangay; Suphanchaimat, Rapeepong; Htun, Wai; Tun Aung, Tin; Khitdee, Chiraporn; Patcharanarumol, Walaiporn; Htoon, Pe; Tangcharoensathien, Viroj
Abstract Background Auxiliary Midwives (AMWs) are community health volunteers supporting the work of midwives, especially maternal and child health services in hard to-reach areas in Myanmar. This paper assessed the contributions of AMW to maternal and child health services, factors influencing their productivity and their willingness to serve the community. Method The study applied quantitative cross-sectional survey using census method. Total of 1, 185 AMWs belonging to three batches: trained prior to 2000, between 2000 and 2011, and in 2012, from 21 townships of 17 states and regions in Myanmar participated in the study. Multiple logit regression was used to examine the impact of age, marital status, education, domicile, recruitment pattern and 'batch of training', on AMW's confidence level in providing care, and their intention to serve the community more than 5 years. Results All AMWs were able to provide essential maternal and child health services including antenatal care, normal delivery and post-natal care. They could identify and refer high-risk pregnancies to larger health facilities for proper management. On average, 9 deliveries, 11 antenatal and 9 postnatal cases were performed by an AMW during the six months prior to this study. AMWs had a comparative advantage for longer service in hard-to-reach villages where they lived, spoke the same dialect as the locals, understood the socio-cultural dimensions, and were well accepted by the community. Despite these contributions, 90 % of the respondents expressed receiving no adequate supervision, refresher training, replenishment of the AMW kits and transportation cost. AMWs in the elder age group are significantly more confident in taking care of the patients than those in the younger groups. Over 90 % of the respondents intended to stay more than five years in the community. The confidence in catering services appeared to have significant association with a longer period of stay in AMW jobs as evidenced by the odds ratio of 3.5, compared to those reporting unconfident. Conclusions Comprehensive support system and national policy are needed to sustain and strengthen the contributions of AMWs, in sharing the workload of midwives, particularly in hard-to-reach areas of Myanmar.